A question of priorities - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
'Look before you leap' is a well-known saying but so is 'easier said than done'. National agricultural systems (NAS) in ACP countries need accurate, quality information to attain local development objectives. Determining exactly what kind of...